Lessons from the geotechnical reconciliation of the B3 cave - Mann, K.; Yanagimura, Y.; Hadjigeorgiou, J. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The geotechnical design of a cave is a complex process that must anticipate considerable changes in stress demand over the life of the cave. This includes the challenges of selecting and applying appropriate design tools, as well as collecting high-quality input data to provide confidence in the analysis results. Continuous improvement of the geotechnical design approach requires reconciling predicted behaviour with observed performance. Systematic, quantitative comparison of predictions and actual responses provides insight into the performance of each design tool and highlights opportunities to refine both the tools and the overall design methodology over time. This paper presents a case study from the B3 extraction level at the New Afton Mine that links geotechnical predictions with observed performance over the life of the cave. It outlines the numerical models, empirical methods, and accumulated site experience used to define the operating strategy and the implementation of mitigation measures. A comprehensive monitoring strategy was employed to evaluate the strengths and limitations of these predictive tools. The paper reviews model assumptions, geotechnical data uncertainty, and operational practices to provide tangible recommendations to improve the design process.